The Effect of Mechanical and Electro-Chemical Treatment on the Corrosion Rate of Austenitic Stainless Steel - Wahyudiono, Arif; Sulistiono, Dety Oktavia; Zain, Alex Taufiqurrohman (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
The aim of this research is to determine the effect of grid blasting and electropolishing on the surface roughness and corrosion rate of AISI 304 stainless steel. In this research, AISI 304 will be treated using surface treatment grid blasting with various variations in blasting time which is then combined with electropolishing. The gritblasting times used in this research were 3, 5, and 7 minutes, and the type of sand used was alumina. Meanwhile, for electropolishing, H2SO4 is used.  Before the grit blasting process is carried out, the material is polished using SiC paper no. 200 and then the surface roughness was measured to be 937 ± 10 µm.  After this the electropolishing process is carried out using an H2SO4 solution. The surface roughness test results showed that the surface roughness decreased with grid blasting time.  Likewise, the data obtained from the corrosion rate is where the corrosion rate also decreases with grid blasting time.